2017
DOI: 10.1590/1516-4446-2017-2239
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising the dimensional structure of the PTSD Checklist: lessons from the DSM-IV-based PCL-C

Abstract: Objective: The dimensional structure of posttraumatic stress disorder (PTSD) has been extensively debated, but the literature is still inconclusive and contains gaps that require attention. This article sheds light on hitherto unvisited methodological issues, reappraising several key models advanced for the DSM-IV-based civilian version of the PTSD Checklist (PCL-C) as to their configural and metric structures. Methods: The sample comprised 456 women, interviewed at 6-8 weeks postpartum, who attended a high-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 42 publications
7
18
0
Order By: Relevance
“…Analysis of the construct of postpartum PTSD found it was best explained by two factors of birth-related symptoms and general symptoms. This is consistent with previous studies of the factor structure of postpartum PTSD which found the same two symptom clusters ( 6 , 26 , 27 ). The symptom subscales of intrusions and avoidance loaded onto the birth-related factor, and the hyperarousal subscale loaded onto the general symptom factor.…”
Section: Discussionsupporting
confidence: 93%
“…Analysis of the construct of postpartum PTSD found it was best explained by two factors of birth-related symptoms and general symptoms. This is consistent with previous studies of the factor structure of postpartum PTSD which found the same two symptom clusters ( 6 , 26 , 27 ). The symptom subscales of intrusions and avoidance loaded onto the birth-related factor, and the hyperarousal subscale loaded onto the general symptom factor.…”
Section: Discussionsupporting
confidence: 93%
“…SRH is an ordinal variable measured on 5-point scale, with 1 = excellent, 2 = very good, 3 = good, 4 = fair, and 5 = poor. Because few respondents reported “fair” and “poor” categories (0.24% reported “poor” and 2.69% reported “fair”), we combined those two groups into one as “poor/fair.” We measured mental health based on responses to screening items of the widely used and validated civilian version of the posttraumatic stress disorder checklist [ 23 ], asking respondents whether, during the past month, they had felt 1) Anhedonia: loss of interest in activities you liked in the past, 2) Sleep problems: difficulty falling asleep, or staying asleep, or waking up frequently or early, 3) Anger: being easily irritable or angry, 4) Difficulty in concentrating, or 5) Repeated disturbing dreams related to COVID-19. Respondents indicate the frequency of each feeling on a 5-point scale of 1 = not at all, 2 = a little, 3 = some, 4 = a lot, and 5 = extremely.…”
Section: Methodsmentioning
confidence: 99%
“…Research examining the factor structure of postpartum PTSD using other measures also finds two factors that are broadly consistent with the City BiTS. For example, Ayers et al (2009) , Stramrood et al (2010) , and Reichenheim et al (2018) identified two clusters of re-experiencing and avoidance and numbing and (hyper)arousal. However, not all studies of postpartum PTSD find this two-factor structure, Olde et al (2006) identified a three-factor structure of intrusion, avoidance and hyperarousal, and a systematic review of PTSD symptoms’ latent structure in other populations even suggests six [e.g., Anhedonia model ( Liu et al, 2014 ) 1 or seven-factor (Hybrid model, Armour et al, 2015 ) 2 models ( Armour et al, 2016 )].…”
Section: Discussionmentioning
confidence: 99%